Examining the Occurrence of the FLASH Effect in Animal Models: A Systematic Review and Meta-Analysis of Ultra-High Dose Rate Proton or Carbon Ion Irradiation - Xun Wu MD; Hongtao Luo MD; Qian Wang MD; Tianqi Du MD; Yanliang Chen MD; Mingyu Tan MD; Ruifeng Liu MD; Zhiqiang Liu MR; Shilong Sun MR; Kehu Yang PhD; Jinhui Tian PhD; Qiuning Zhang MD (Technology in Cancer Research & Treatment)
Purpose: This systematic review and meta-analysis sought to assess whether ultra-high dose rate (UHDR) ion irradiations can induce the FLASH effect in animal models. Methods: A comprehensive search of the Web of Science, PubMed, and EMBASE databases was conducted from inception until March 20, 2023, to identify studies involving irradiated animals subjected to proton or carbon ion beams at varying dose rates. The research content should include various indicators that can reflect the effect and safety of radiation, such as survival, normal tissue toxicity, inflammatory response, tumor volume, etc Results: Compared to conventional dose rate (CONV) ion irradiations, UHDR ion irradiations can significantly improve mouse survival (HR 0.48, 95% CI 0.29 to 0.78, I 2  = 0%) and maintain comparable tumor control. There was no significant impact of different dose rates on the survival of zebrafish embryos (SMD 0.11, 95% CI −0.31 to 0.53, I 2  = 85%). Subgroup analysis showed that radiation dose was an important factor affecting the survival of zebrafish embryos. Achieving normal tissue sparing may require higher radiation dose under UHD.In mouse and zebrafish embryo models, normal tissue sparing did not always occur after UHDR ion irradiations. In addition, only a limited number of cytokines (CXCL1, IL-6, GM-CSF, G-CSF, HMGB1, and TGF-β) and immune cells (microglia and myeloid cells) showed differences at different dose rates. Conclusions: UHDR ion irradiation can achieve FLASH effect, but the reproducibility of normal tissue sparing remains a challenge. Compared to CONV irradiation, UHDR ion irradiations demonstrated equivalent or even superior tumor control.